Identification of Protein Kinase C Isoforms Involved in Type 1 Diabetic Encephalopathy in Mice - Jiayin Zheng; Yue Wang; Song Han; Yanlin Luo; Xiuli Sun; Ning Zhu; Li Zhao; Junfa Li (Journal of Diabetes Research)
Diabetic encephalopathy is a complication of diabetes mellitus characterized by impaired cognitive functions. Protein kinase C (PKC) isoforms are rarely reported on diabetic encephalopathy, although they have been believed to play crucial roles in other diabetic complications. In this study, streptozotocin- (STZ-) induced diabetic mice were found to exhibit learning and memory deficits in the Morris water maze test. Meanwhile, the expression of cPKCβII, nPKCε, and cPKCγ did not change in the hippocampus, cortex, and striatum at 2 and 8 weeks after STZ injection. The nPKCε translocation to the membrane, where it is activated, was not altered in the above brain regions at 2 and 8 weeks after STZ injection. Nevertheless, cPKCβII translocation to the membrane was significantly decreased in the cortex and hippocampus at 8 weeks after STZ injection. The translocation of cPKCγ from the cytosol to the membrane was remarkably decreased in the hippocampus at 2 and 8 weeks and in the cortex and striatum at 8 weeks after STZ injection. In addition, deletion of cPKCγ aggravated the impairment of spatial learning and memory. In conclusion, our results suggest that the decrease in the activity of cPKCβII and cPKCγ, especially cPKCγ, may play key roles in the pathogenesis of diabetic encephalopathy.